2(x-5)+7=6x-4(1+x)

Simple and best practice solution for 2(x-5)+7=6x-4(1+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-5)+7=6x-4(1+x) equation:


Simplifying
2(x + -5) + 7 = 6x + -4(1 + x)

Reorder the terms:
2(-5 + x) + 7 = 6x + -4(1 + x)
(-5 * 2 + x * 2) + 7 = 6x + -4(1 + x)
(-10 + 2x) + 7 = 6x + -4(1 + x)

Reorder the terms:
-10 + 7 + 2x = 6x + -4(1 + x)

Combine like terms: -10 + 7 = -3
-3 + 2x = 6x + -4(1 + x)
-3 + 2x = 6x + (1 * -4 + x * -4)
-3 + 2x = 6x + (-4 + -4x)

Reorder the terms:
-3 + 2x = -4 + 6x + -4x

Combine like terms: 6x + -4x = 2x
-3 + 2x = -4 + 2x

Add '-2x' to each side of the equation.
-3 + 2x + -2x = -4 + 2x + -2x

Combine like terms: 2x + -2x = 0
-3 + 0 = -4 + 2x + -2x
-3 = -4 + 2x + -2x

Combine like terms: 2x + -2x = 0
-3 = -4 + 0
-3 = -4

Solving
-3 = -4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8(c-2)+4=3+c-15 | | 4x+6.46=2x+10 | | x^2-30x-63=0 | | 0.2x+0.1=0.12-0.06 | | 2x-17=14x+1 | | 10x-7=3x+8 | | 6x-(2x+8)=3x+(x+6) | | y=0-5x | | 500=55n-35n | | 4(n+4)=-2(4+2n) | | x+21=23+5x | | X^2+6=25 | | x+2.1=8.3 | | 1.5=0.8 | | -1-2(x+1)=3-2x | | 7x+9=-2x+55 | | (100-4Z)20= | | 3x+x-8=4 | | x-1=1.26 | | -12n+10=-8+2 | | 4x+8+(-3x)=20 | | 4x-1+5x+2=90 | | 8(2n+1)=8(4n+1)+5 | | 4x-1+5x+2=180 | | -2+3(x-1)=-5+3x | | -5y=2.55 | | f(x)=x+4f(-7) | | 4x+yminush=10y+u | | 4x-1+5x+2+8x=7 | | 4(X-2)=6-(3-2X) | | 10x^2+2*x-26=4 | | x+2=(sqrtx+7)+2 |

Equations solver categories